Thermogravimetric and Kinetic Analysis of Cassava Starch Based Bioplastic - Nanang Eko Wahyuningtyas; Heru Suryanto; Eddy Rudianto; Sukarni Sukarni; Poppy Puspitasari (Universitas Negeri Malang, 2017)
Cassava starch based bioplasticfor packaging application has great potency because of the various starch-producing plants in Indonesia.Bioplasticcan contribute to reduce the dependence on fossil fuels andpetroleumthat can solve the environmentalproblem.Thepurpose of this research is to find out the thermal decomposition and the activation energy of cassava starch based bioplastic. The methods weresynthesis bioplastic with cassava starch as main component and glycerol as plasticizer. The thermogravimetry analysis was conducted to obtain the decomposition process mechanism of bioplastic and the heating valueof bioplasticwas measured using theadiabatic bomb calorimetric. Data analysis was conducted using a fitting model approach with an acikalin method to determine the activation energy. The result of thethermogravimetricanalysis showed thatbioplasticisgraduallydecomposedto the moisture, volatilematter, fixed carbon, andash in four stages mechanism. Totally decomposition of bioplastic was 530°C, then all of bioplastic was become the ash. The activation energy in the early and primary thermal decomposition stages are 1.27 kJ/moland 22.62 kJ/mol, respectively and heating valueof bioplastic is 15.16 MJ/kg.